Determinants that influence the performance of women entrepreneurs in micro and small enterprises in Ethiopia - Endalew Terefe Alene (Journal of Innovation and Entrepreneurship, 2020)
Purpose: The purpose of this study was to explore determinants that influence women entrepreneurs' performance in micro and small enterprises in Gondar city, Northwest Ethiopia, and in turn contribute to entrepreneurship-related literature mainly in developing countries.Design/methodology/approach: The study employed an explanatory research design with agreement of primary data collection via a cross-sectional survey questionnaire followed by quantitative research approach. The sample of this study was 180 women entrepreneurs and selected using random sampling technique. Findings: The findings of this study revealed that educational level, previous entrepreneurial experience, access to business training, access to finance, access to business information, government support, land ownership, and tax are significant in explaining women entrepreneurs' performance in one hand. On the other side, however, age, marital status, access to market, and access to physical infrastructure are found to be insignificant variables in determining women entrepreneurs'performance. Research limitations/implications: The study used one time data for determinants like level of education, previous working experience, age, and profitability of the enterprise. Thus, due to frequent change in such variables, the study may not reflect the dynamics of the data, which would have a convincing influence on the conclusion. In addition, the research has only consisted of 180 samples. Moreover, such number may not represent the whole population of the entrepreneurs of Ethiopian MSEs. In future research, it is advisable to expand study factors, use interviews as a research tool, and make a comparison between women and men entrepreneurial performances. Practical implications: The paper might serve as an input for officials to consider such determinants and encourage an environment that increases women entrepreneurs' performance. In addition, the study might help women entrepreneurs in addressing the factors affecting performance to take actions towards improving their performance and in turn contribute to job creation, wealth, innovation, and poverty alleviation. Originality/value: This study contributes to the literature on the determinants of women entrepreneurs' performance in micro and small enterprises. Specifically, it tests the impact of educational level, age, marital status, previous entrepreneurial experience, access to business training, access to finance, access to business information, access to market, access to physical infrastructure, government support, land ownership, and tax on the performance of women entrepreneurs.
Keywords: 650; Women entrepreneur; Performance; Gondar city; Micro and small enterprise; Determinant